1996
DOI: 10.3109/00365529609006775
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Duct Abnormalities and Pancreatic Function in Patients with Chronic Inflammatory Bowel Disease

Abstract: Our results show the presence of pancreatic duct abnormalities and exocrine pancreatic insufficiency in some patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
9

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 35 publications
1
48
0
9
Order By: Relevance
“…By using the secretin-cerulein test, Angelini et al [11] found a decrease in bicarbonate and enzyme output in 11 among 27 patients and an isolated decrease of lipase output in 18/27 patients in a series of 27 patients with IBD. Heykius et al [6] , in a series of patients with UC or CD, found abnormal PABA test results in 21.8 and 26% of the cases. In IBD patients, Hegnhoj et al [12] confirmed a significant decrease of amylase and lipase output with Lundh meal test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By using the secretin-cerulein test, Angelini et al [11] found a decrease in bicarbonate and enzyme output in 11 among 27 patients and an isolated decrease of lipase output in 18/27 patients in a series of 27 patients with IBD. Heykius et al [6] , in a series of patients with UC or CD, found abnormal PABA test results in 21.8 and 26% of the cases. In IBD patients, Hegnhoj et al [12] confirmed a significant decrease of amylase and lipase output with Lundh meal test.…”
Section: Discussionmentioning
confidence: 99%
“…None of them had previous clinical evidence for pancreatic disease, suggesting subclinical or silent alteration of the pancreas. The relationships between pancreatitis and the extent and severity of [2,6,20] . Such data and the recent evaluation of standardized incidence ratios of pancreatitis, 4.3 for CD and 2.1 for UC [21] , led to the conclusion that many cases of IBD-associated pancreatitis are extraintestinal manifestations of the intestinal disease [2,22] but with an unknown or controversial frequency when considering clinical, biological or radiological data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Octanoic acid is absorbed without further requirements as soon as it enters the duodenum. As a consequence, potentially decreased pancreatic exocrine function as observed in IBD (22,25) is irrelevant. Because we did not have evidence for involvement of the proximal gastrointestinal tract apart from small ulcers and/or histological lesions in two patients with CD (Table 1), we conclude that the 13 C-OABT reliably reflected gastric emptying of solids in our patients.…”
Section: Performance and Reliability Of Gastric Emptying Testmentioning
confidence: 99%